Key-texts in the epistle to the Hebrews - Loane, Marcus Lawrence, 1911- (London, UK Marshall, Morgan and Scott, 1961)
Includes bibliographical references.
Keywords: Bible. N.T. Hebrews -- criticism, interpretation, etc